Fulfilling the Promise : Virginia Commonwealth University and the City of Richmond, 1968-2009 - Kneebone, John T.; Trani, Eugene P. (Book collections on Project MUSE., 2020)
"A definitive history of Virginia Commonwealth University, providing insight into the growth and role of urban universities writ large"--